Causes and Characteristics of Possible Flood Occasions in the Yevlax-Neftchala Zone along the Kura River Basin - Huseynov, H.A.; Safarov, S.H. (Herald of Azerbaijan Engineering Academy, 2024)
Floods, which are among the most advanced natural disasters that occur in Azerbaijan and the world in terms of percentage, cause great damage to the country's economy, as well as human casualties and material losses. The overflow that occurred in the country is mainly manifested as a result of floods. The Yevlakh-Neftchala zone, taken as the study area, is the region most exposed to the threat of flooding, and especially the predominance of agricultural areas in these areas results in the overflow of farmland in cases of flooding. Because of this, hectares of crop and agricultural fields are flooded, causing considerable (100 million manats) financial damage to the country's economy. In the article, the causes and characteristics of possible floods in the Yevlakh-Neftchala zone along the Kura river basin were investigated, the characteristics of previous floods were studied, and the reasons for their occurrence were analyzed and evaluated.